Pemasaran Produk Kembang Tahu Menggunakan Marketing Mix - Dewanti , Agilia Putri Ayu (Jurnal Kewirausahaan dan Bisnis, 2024)
The marketing mix paradigm, in its famous version of the 4Ps, went all the way through the evolution of marketing theory: from the marketing concept, through relationship marketing, to digital economy, being object of discussion both in academic literature and managerial practice. If it is a fact that the 4Ps marketing mix is a milestone of marketing theory, it is also true that the evolution of business contexts has created, in many fields, the need to review the "controllable factors" which form the marketing mix. The digital business represents the more recent of the business contexts and the one with the greater needs of differentiation of the mix. Throughout this evolutionary process, researchers have always been divided between the "conservatives," who think the 4Ps paradigm is able to adapt to the environmental changes by including new elements inside each "P," and the "revisionists," who affirm that the 4Ps paradigm is obsolete and propose new paradigms. This paper aims to clarify these two different approaches to marketing mix evolution through a review of the main literature on e-marketing mix, focusing on the development of marketing mix theory for the digital context. Business is an activity that requires a serious understanding, ranging from planning what will be made later in the stage of implementation, monitoring, and evaluation. An important step that can be taken by business people is to plan a strategy, so the goal in doing business to gain profit and prosperity can be achieved. One strategy that can be applied in business is the marketing mix strategy. This is a strategy of how to apply 4Ps consisting of product, price, promotion and place. Products created should be halal and needed by society, and product quality is something important for business people to consider. The price of a product has also become a serious matter that should be managed properly to make it reasonable and competitive and free of usury. The promotion is geared to encourage purchases by creating a positive impression of a product that consumers are persuaded to make a purchase without deception. The place can also be defined as the location of the company. The location of a company/business organization should be easily accessible by the public, such as around shopping centres and so forth so as to avoid the interception action by the speculators before marketing. A business person should be able to choose a location that serves to represent the company and can be accessed by the public.